PENANAMAN SIKAP NASIONALISME PADA PEMBELAJARAN TEMATIK KELAS IV MADRASAH IBTIDAIYAH AL-IHSAN KAYUARU - M. Syafiuddin Hanafi; Devi Wahyu Ertanti; Bagus Cahyanto (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Instilling an attitude of nationalism to students aims to uphold the values of nationalism. This can be seen from his lack of morals, character and love for the Indonesian people. This can be indicated by the students' lack of ethics towards teachers, unable to use good Indonesian and not being able to sing the national anthems properly and correctly. The decline in attitudes of nationalism can be seen from students who do not memorize the Indonesian independence anthem, they sing it with reversed lyrics, and the students' lack of order in participating in the flag ceremony. The formulation of the problem in this study: 1) What are the teacher's strategies in instilling an attitude of nationalism loving the homeland and nation through thematic learning of theme 1 in class IV MI Al-Ihsan Kayuaru, 2) What is the teacher's strategy in instilling an attitude of nationalism in the nation's cultural diversity through thematic learning theme 1 in class IV MI Al-Ihsan Kayuaru, 3) What is the teacher's strategy in instilling an attitude of nationalism in togetherness and diversity in class IV MI Al-Ihsan Kayuaru. The approach used is descriptive qualitative with the type of case study research, with the method of observation, interviews, and documentation. The attitude of nationalism must be owned by every citizen. This is due to the importance of the attitude of nationalism in maintaining the integrity of a nation. Keywords: Attitude of Nationalism, Planting, Thematic Theme 1.